2001
DOI: 10.1177/000331970105200204
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Interleukin-1 Beta, Interleukin-6, Tumor Necrosis Factor-Alpha, and Soluble ICAM-1 in Patients with Chronic Stable Angina and Myocardial Infarction

Abstract: The changes in serum concentrations of cytokines such as interleukin-1 (IL-1) beta, interleukin-6 (IL-6), tumor necrosis factor (TNF) alpha and a soluble-intercellular adhesion molecule (sICAM-1) has been investigated in patients with stable angina and acute myocardial infarction. Thirty-four patients with stable angina (SA), 15 with acute myocardial infarction (AMI), and 20 subjects in the control (C) group were included in the study. The mean serum concentrations of sICAM-1, IL-1-beta, IL-6, and TNF-alpha di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 24 publications
3
28
2
1
Order By: Relevance
“…The mRNA and protein expressions of IL-1β and TNF-α in the brains were markedly lower, but the mRNA and protein expressions of IL-10 and IL-10R in the brains were markedly higher in the GbE 100 mg/kg group than that in the AS group. Our results were consistent with the recent findings that the serum levels of TNF-α and IL-1β in all patients with coronary heart diseases were higher than those in controls [7][8][9] . IL-10 was an anti-inflammatory cytokine with powerful immunoregulation potential [10] .…”
Section: Discussionsupporting
confidence: 93%
“…The mRNA and protein expressions of IL-1β and TNF-α in the brains were markedly lower, but the mRNA and protein expressions of IL-10 and IL-10R in the brains were markedly higher in the GbE 100 mg/kg group than that in the AS group. Our results were consistent with the recent findings that the serum levels of TNF-α and IL-1β in all patients with coronary heart diseases were higher than those in controls [7][8][9] . IL-10 was an anti-inflammatory cytokine with powerful immunoregulation potential [10] .…”
Section: Discussionsupporting
confidence: 93%
“…The present study has demonstrated elevation of plasma levels of TNF-a and IL-6 as a result of AMI, which is in accord with many prior reports [3][4][5]15,17,[19][20][21][22][23][24][25][26]. The time course of cytokine activation in AMI reflected by increased gene expression in heart muscle or elevated plasma concentrations varied from 2 to 40 days in different studies [2,[26][27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 92%
“…IL-6 depresses myocardial function predominantly by activation of iNOS and partially by stimulation of intercellular cell adhesion molecule (ICAM-1) with accumulation of neutrophiles and subsequent neutrophile-dependent myocardial injury [1,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Other data from the same study groups (62) and data from an additional study of early effects of ICV SL (60) suggest that the SL acts centrally to reduce sympathetic drive in HF rats. failure and MI literature, the most studied of the proinflammatory cytokines are TNF-␣, interleukin-6, and interleukin-1␤ (6,38,39,84,118,131). In our rat model (61), blood-borne TNF-␣ increases as early as 30 min after coronary artery ligation.…”
Section: The Cytokine Connectionmentioning
confidence: 99%